Conquiologia e anatomia de Orthalicus pulchellus (Spix,1827) (Mollusca, Gastropoda, Pulmonata, Orthalicidae) - Araujo, Ana Cristina de (1998)
Studies on shell, Jaw, radula, palial camera roof and reproductive system are presented, including macro and microanatomical characterizations of the penis appendix, what enabled the characterization and distinction of Orthalicus pulchellus (Spix, 1827) from the other known species of Orthalicidae for Brazil. The material examined allowed the enlargement of the geographical distribution of the species; Ceará, Paraíba, Alagoas, Mato Grosso, Minas Gerais and Espírito Santo. Bibliographical data and observations on terraria allowed us to examine that the animal feed itself scratching fungi and lichens from the surfaces of small trunks and branches of several plant species.